Discerning the Putative U and V Chromosomes of Saccharina japonica (Phaeophyta) by Cytogenetic Mapping of Sex-Linked Molecular Markers - Yu Du; Peng-Fei Liu; Zhi Li; Qian Zheng; Yan-Hui Bi; Zhi-Gang Zhou (Frontiers in Marine Science, 2022)
Saccharina japonica, an importantly industrial species in brown seaweeds, has a typical alternate life history of heteromorphic generations and UV sex determination system. But up to now, the sex chromosomes, U and V, in this kelp remain to be evidenced cytologically. In the present study, the female-linked (SJ-f_000170 and MSj68-58-2) and male-linked (SJ-13_001840 and MSj68-16-2) molecular markers developed on the basis of Ectocarpus sex-determining regions (SDRs) were selected after PCR amplification and Southern blotting analysis. Mono-color fluorescence in situ hybridization (FISH) to the kelp metaphase chromosomes with each of these confirmed sex-linked markers as a probe indicated that the hybridization signals were confined to either female or male gametophytes exclusively. The shape and size of hybridized chromosomes and the relative location of these sex-linked markers on them suggested that the marked chromosomes in a sex were the same, which was further confirmed by dual-color FISH observations. SJ-f_000170 and SJ-13_001840, corresponding to each sex, were therefore used to map the sporophyte metaphase chromosomes by dual-color FISH technique, and they were hybridized on different chromosomes as expected. The sporophyte metaphase chromosomes as hybridized by SJ-f_000170 and SJ-13_001840 resembled those in either female or male gametophytes, suggesting that they were the putative U and V, respectively, chromosomes in S. japonica. To further demonstrate the reliability of this inference, genomic information of the screened bacterial artificial chromosome (BAC) clones carrying two female-linked markers, for example, from the constructed BAC libraries of the kelp female gametophytes was provided. The insert sequencing of two selected BAC clones revealed that repetitive elements were rich whereas gene density was poor, which was characterized as non-recombining SDR sequences in brown seaweed Ectocarpus sp. and liverwort Marchantia polymorpha. The present study laid a solid foundation for unveiling the mystery of S. japonica sex chromosomes.